What do we know about the long term medication adherence in patients following percutaneous coronary intervention - Fernandez, R.; Davidson, Patricia; Griffiths, R.; Juergens, C.; Salamonson, Y. (Wiley-Blackwell Publishing Ltd, 2007)
Background Percutaneous coronary intervention (PCI) is a revascularisation intervention for patients with acute coronary syndrome. It is a common procedure, increasingly used over the past decade. Along with PCI, patients are also prescribed a number of medications and adherence to the pharmacological therapies is vital to improved morbidity and mortality. Objective This cross-sectional study sought to evaluate the long term adherence to medications in patients following PCI. Subjects 270 participants who underwent PCI between April 2003 and March 2004 and who met the inclusion criteria were followed up 12-24 months following the PCI. Methods Following obtaining informed consent, a self administered questionnaire was mailed to participants. Information was collected relating to the types of medications taken, medication taking behaviours and storage of medications. Results Overall high rates of self-reported medication adherence were reported. In spite of this, patients continued to miss medications or reported stopping medications if they felt better or worse. Knowledge of storage of medication in particular nitro-glycerine medications was poor. Conclusions Findings suggested that following PCI medication adherence is high, however knowledge about medication storage is limited and patients report cessation of medications which they consider to be deleterious or unnecessary. These findings are useful for informing development of nursing interventions.